Antimicrobial action, pH, and tissue dissolution capacity of 2.5% sodium hypochlorite gel and solution - Luz, Luciana Batista; Santana, Ruth; Prates, Amanda Westphal; Froelich, Julia; de Melo, Tiago André Fontoura; Montagner, Francisco; Luisi, Simone Bonato (Journal of Health & Biological Sciences, 2019)
Introduction: The aim of this study was to evaluate antimicrobial action, pH, and tissue dissolution capacity of 2.5% sodium hypochlorite (NaOCl) gel and solution. Methods: The 2.5% NaOCl gel was produced from a colloidal base. The test groups included 2.5% NaOCl gel and solution and the control groups included gel base and distilled water. The antimicrobial activity was evaluated by the broth dilution technique against Enterococcus faecalis (ATCC 29212) at 15 and 30 seconds and at 1, 5, and 10 minutes. To evaluate tissue dissolution capacity, 30 pulp fragments of bovine incisors were weighed, 10 for each test group and 5 for each control group before and after exposure to the chemical auxiliaries. The final mass percentage of each fragment was calculated. The pH of the substances was measured in triplicate through a digital pH meter. Results: pH levels of 13.08 and 9.75 were observed for 2.5% NaOCl solution and gel, respectively. The antimicrobial action of 2.5% NaOCl was the same for both solution and gel, for all tested times. The 2.5% NaOCl solution group showed higher tissue dissolution capacity (Kruskal-Wallis and Student-Newman-Keuls tests P<0.0001). Conclusions: The type of medium, either solution or gel, containing 2.5% NaOCl did not influence the antimicrobial action at any of the tested times. However, 2.5% NaOCl gel did not present tissue dissolution capacity.